Interorganizational cooperation and intraorganizational power: Early agreements under codecision and their impact on the Parliament and the Council - Henry Farrell; Adrienne Héritier (Max-Planck-Projektgruppe Recht der Gemeinschaftsgüter, 2002)
Current research on the main bodies of the European Union (Council, Commission, Parliament) tends to concentrate either on relations within these bodies, or on relations between them. The result is that little attention is paid to how these two intersect; that is, to how changes in relations between bodies can affect relations among them, and vice versa. In this article, we examine the effects of the introduction of the codecision procedure on relations between the Council and the Parliament. We show that the changes in informal and formal relations between Council and Parliament associated with codecision have affected power relations within Council and Parlia-ment in important ways. In a second stage of development, actors who have been disadvantaged by these changes have sought to redefine relations yet again in order to restore their power over legislative outcomes.
Keywords: 330